Performance of beans after inoculation with azospirillum brasilense and rhizobium tropici, and nitrogen and molybic fertilizations under amazonian conditions - De Melo Filho, Luiz Cobiniano; Henrique, Ivanildo Guilherme; Arf, Orivaldo [UNESP]; De Oliveira, Darllan Junior Luiz Santos Ferreira [UNESP]; DeLima, Antonio Anicete; MacEdo, Marcos Aurélio Anequine; Mendes, Juliana Pereira; De Lima Oliveira, Romário Batista (Universidade Estadual de Londrina, 2020)
Beans are nutrient-demanding plants, with a high demand for nitrogen (N). Nitrogen biological fixation (NBF) is probably the best solution to meet this demand, especially considering losses in the soil-plantatmosphere system. Molybdenum (Mo), present in the enzymes nitrogenase and nitrate reductase, is fundamental in the metabolism of N, including NBF. This study aims to evaluate if bean seed inoculation with Azospirillum brasilense, Rhizobium tropici, and possible interactions with nitrogen topdressing and molybdenum leaf application, may affect winter bean development and yield. A randomized complete block design was used in a 4x2x2 factorial scheme. Plant population, production components, and grain yield were evaluated in two crop seasons (2017 and 2018). Seed inoculation with A. brasilense, when associated with 30 kg ha-1 N topdressing, increased plant population, pod number per plant and grain yield. Nitrogen topdressing is key to increasing winter bean productivity, regardless of inoculation or Mo foliar application.
Keywords: Co-inoculation; Diazotrophic bacteria; Phaseolus vulgaris L